Evaluation of feto-maternal outcome using AFI and SDVP for amniotic fluid assessment; Which is a better method? - Mukhopadhyay, Biplab; Ahmad, Syed Nawaz; Agarwal, Shefali; Kabra, Shashi Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
ABSTRACT Background: Abnormal amniotic fluid volume (AFV) may be the only or earliest sonographic sign of an obstetrical problem. There is no clear consensus on the best method to assess amniotic fluid adequacy. The AFI and the SDVP are the more commonly employed techniques for assessing adequacy of amniotic fluid. This study aimed to compare the maternal and foetal outcome when amniotic fluid was measured by these two methods. Methods: Hundred pregnant women at >28 weeks gestation scheduled for test of biophysical score due to various risk factors were enrolled and divided in two groups of 50 each. In each group, amniotic fluid volume was determined by either calculating the Amniotic Fluid Index (AFI) or measuring the Single Deepest Vertical Pocket (SDVP). Oligohydramnios was declared at cut off of <5 for the former and <2cm for the later method respectively. Maternal and foetal outcomes were compared between the two groups. Results: Diagnosis of oligohydramnios was 45/50 in group I and 23/50 in group II (p<0.0001). Induction of labour was done in 70.0% in group I and 18% in group II (p<0.0001). Non-reassuring foetal heart rate was seen in 36.0% in group I and 14.0% in group II (p=0.011). Rate of caesarean delivery was significantly higher in group I, 42.0% in comparison of 20.0% in group II (p=0.017). NICU admission were 32.0% in group I and 18.0% in group II (p=0.106). Conclusions: SDVP is a better choice for determining amniotic fluid to avoid unnecessary interventions without any significant improvement in peripartum outcome measures.